Multimodal Discourse Analysis in Learning Media: A Case Study of Promotional Content in Pasuruan - Mochamad Bayu Firmansyah; Suchaina Suchaina; M. Ridwan (STAI Hubbulwathan Duri, 2025)
Pasuruan, known for its rich cultural heritage and natural beauty, requires more effective promotional strategies that authentically reflect its local identity. Current tourism materials often lack depth in portraying the region’s historical and cultural dimensions. This study investigates how multimodal promotional content can better communicate Pasuruan's cultural narrative while also serving as educational media. This qualitative study employed a multimodal discourse analysis approach, examining 215 brochures, 3,500 website posts, and guidebooks related to Pasuruan’s tourism. The analysis focused on five core modalities—language, images, music, sound, and movement—and was guided by seven thematic categories, including nature, religion, authenticity, and persuasive strategies. Findings reveal that promotional content effectively combines various modes to depict the interconnection between Pasuruan’s society, religious traditions, and natural environment. Rituals such as Petik Laut and religious landmarks are emphasized through compelling visual and textual representations. The materials successfully evoke authenticity and emotional appeal, enhancing both cultural understanding and tourist interest. Multimodal promotional content not only informs but also engages audiences through layered communication strategies. These materials offer more than tourism promotion—they support multimodal learning, making them valuable in educational settings, particularly in tourism and cultural studies. This study highlights the potential of multimodal media in promoting local culture while enriching tourism education. The findings advocate for integrating multimodal approaches into both promotional practices and learning frameworks, supporting culturally respectful and effective communication strategies in the tourism industry.